Agricultural sub-sectors in new and updated NDCs: 2020-2024 - Dittmer, Kyle Michael; Rose, Sabrina Catherine; Khatri-Chhetri, Arun; Stier, Melina; Trang, Vu Hong; Nelson, Katherine (2024)
Data presented here are the result of an analysis of agricultural sub-sectors within new and updated NDCs. This analysis covers 176 new or updated NDCs submitted as of November 30, 2024. NDCs are available for download at https://www4.unfccc.int/sites/NDCStaging/Pages/All.aspx. This analysis does not include first round NDCs that were not updated. For a database of the first NDCs created in 2016, see Richards et al. (2016) and for NDCs up through February 5, 2019 see Richards et al. (2019) (see References below). While every effort has been made to ensure the completeness and accuracy of this data set, please contact K.Dittmer@cgiar.org if you notice any inaccuracies in livestock or soil and t.h.vu@irri.org if you notice any inaccuracies in rice. What has changed in this version? Version 2.2 [1-Dec-24] This version includes new data for the soil carbon, livestock, and rice sub-sectors, financial needs related to the soil carbon, livestock, and rice sub-sectors, and alignment with the Global Methane Pledge for livestock and rice sub-sectors from new or updated NDCs submitted as of November 30, 2024.notice any inaccuracies in livestock